Sustained Activation of Wnt/β-Catenin Signaling Drives AKI to CKD Progression - Liangxiang Xiao; Dong Zhou; Roderick J. Tan; Haiyan Fu; Lili Zhou; Fan Fan Hou; Youhua Liu (2015)
AKI is increasingly recognized as a major risk factor for progression to CKD. However, the factors governing AKI to CKD progression are poorly understood. In this study, we investigated this issue using moderate (20 minutes) and severe (30 minutes) ischemia/reperfusion injury (IRI) in mice. Moderate IRI led to acute kidney failure and transient Wnt/ β -catenin activation, which was followed by the restoration of kidney morphology and function. However, severe IRI resulted in sustained and exaggerated Wnt/ β -catenin activation, which was accompanied by development of renal fibrotic lesions characterized by interstitial myofibroblast activation and excessive extracellular matrix deposition. To assess the role of sustained Wnt/ β -catenin signaling in mediating AKI to CKD progression, we manipulated this signaling by overexpression of Wnt ligand or pharmacologic inhibition of β -catenin. In vivo , overexpression of Wnt1 at 5 days after IRI induced β -catenin activation and accelerated AKI to CKD progression. Conversely, blockade of Wnt/ β -catenin by small molecule inhibitor ICG-001 at this point hindered AKI to CKD progression. In vitro , Wnt ligands induced renal interstitial fibroblast activation and promoted fibronectin expression. However, activated fibroblasts readily reverted to a quiescent phenotype after Wnt ligands were removed, suggesting that fibroblast activation requires persistent Wnt signaling. These results indicate that sustained, but not transient, activation of Wnt/ β -catenin signaling has a decisive role in driving AKI to CKD progression.